Islamic Psychology and Quranic Ethics: A Framework for Developing Resilience and Coping Skills in the Modern World - mursidin mursidin (UIN Sunan Gunung Djati Bandung, 2023)
This research study highlights the paramount significance of Quranic ethics within the domain of Islamic psychology, particularly in addressing the psychological challenges of contemporary society. By recognizing the crucial role played by spirituality and ethical behavior in mental well-being, Islamic psychology offers a valuable framework for promoting comprehensive wellness and social equity. This study employs a qualitative research approach and follows a systematic methodology comprising several key steps, including literature review, data collection, data analysis, framework development, and validation. The findings of this study demonstrate that Islamic psychology and Quranic ethics provide a distinct and invaluable perspective on human behavior and mental health, addressing the unique challenges faced by individuals in the modern world. As the primary source of Islamic teachings, the Quran serves as the foundational basis for the framework of Islamic psychology, offering a holistic approach to understanding human beings. Notably, the Quran presents a comprehensive set of moral guidelines that can be applied and developed within the context of Islamic psychology. The framework of Quranic ethics encompasses various dimensions, including moral guidance, virtues and character development, self-reflection and accountability, spiritual well-being, ethical decision-making, and healing/forgiveness. By incorporating Quranic guidance on moral conduct, virtues, self-reflection, and forgiveness, Islamic psychology provides practical solutions that acknowledge the profound significance of spirituality. This integration empowers individuals to derive strength, discover meaning, and establish a sense of purpose through their faith.